Synthesis and characterization of low molecular mass amphiphilic block copolymers and potential use in surfactant assisted particle micro-mixing - Focke, Walter Wilhelm (University of Pretoria, 2013)
Dissertation (M Eng (Chemical Engineering))--University of Pretoria, 2006.